DEVELOPMENT OF AN INTELLIGENT ONLINE PLATFORM FOR AUTONOMOUS LEARNING IN SOFTWARE DEVELOPMENT AND DIGITAL DESIGN - Atadjanov H. (European Science Publishing, 2024)
This article explores strategies for structuring self-directed learning in the field of educational technology. The authors discuss innovative approaches and modalities for using information technologies, including Web2.0 and Web3.0, to enhance the educational experience. In addition, the article explores the integration of case-based learning and project-based methodologies within educational frameworks.
Keywords: Self-directed learning, educational technology, Web2.0, Web3.0, case-based learning, project-based learning, electronic educational resources.